Analisis Efektivitas Pelaksanaan Ekstensifikasi Pajak Dalam Rangka Meningkatkan Penerimaan Pajak Di Kantor Pajak Pelayanan Pratama Jakarta Matraman Tahun 2020-2021 - Bunga Indah Andar; Roike Tambengi (Jurnal Ilmu Administrasi Publik, 2023)
Tax is a potential state revenue, and the target of tax revenue from year to year continues to increase. One of the efforts to increase tax revenue is to implement a tax extensification program. The tax extensification program is an activity related to increasing the number of new taxpayers through the provision of NPWP (TIN). Some of the taxpayer extensification activities owned by the Primary Tax Office of Matraman, Jakarta include: 1) Data and Field Collection Activities (KPDL), 2) direct exploration to work areas, 3) campaigns through the events of bazaars or seminars for business actors, and 4) services through social media to make it easier to spread knowledge about taxation to taxpayers. This study uses Duncan's theory of effectiveness with indicators of goal achievement, integration, and adaptation. This study used a qualitative descriptive approach, the purpose of which was to analyze the effectiveness of the implementation of taxpayer extensification as an effort to increase tax revenue at the Primary Tax Office of Matraman, Jakarta in 2020-2021; the obstacles that arose; and the efforts that need to be made in carrying out mandatory tax extensification activities. The results of this study indicate that the taxpayer extensification activities and programs that have been implemented by the Primary Tax Office of Matraman, Jakarta have been running effectively and in accordance with applicable laws. This is indicated by the number of new taxpayers resulting from extensification which continues to increase during 2020-2021. The inhibiting factors are the lack of knowledge and awareness of taxpayers on the importance of having a NPWP as well as the limited and incomplete taxpayer data owned by the Primary Tax Office of Matraman, Jakarta. The efforts made by the Primary Tax Office of Matraman, Jakarta to maximize tax extensification activities are collaborating with relevant parties to obtain taxpayer data and conducting campaigns to provide education and understanding to taxpayers about taxation in the hope of increasing their awareness.